Information privacy and performance appraisal: An examination of employee perceptions and reactions - Mossholder, Kevin W. (Journal of business ethics, 1991)
Role-failure acts (Waters and Bird, 1989) have been described as a form of morally questionable activity involving a failure to perform the managerial role. The present study examined employee perceptions and reactions with regard to one form of role-failure act, failure to maintain adequate privacy of performance appraisal information. The study assessed employees' attitudes toward various performance appraisal facets as an invasion of privacy and determined the relationships between these privacy-related attitudes and employees' satisfaction with components of their appraisal system, the system as a whole, and their jobs. Responses that organizations might take to counteract appraisal privacy concerns were also discussed.